The Challenges And Contribution Of Internet Of Things (IoT) For Smart Living - Marjumin, N.H.; Sidek, Safiah; Abu Hassan, Mahadi; Kudus, Norliah; Mohamed, Shahrulanuar; Rajikon, Muhd Akmal Noor; Kamalrudin, Massila (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The evolution of Internet and advanced in ICT had led to the increasingly usage of Internet of Things (IoT) in various sectors and facilitated borderless connection in various fields. Contextualised within the development of Smart City, much have been reported on the challenges and contribution of using of IoT for smart living. This paper presents a review of the challenges and contribution of using IoT for smart living. Using a systematic method to analyse the literature, 31 articles have been selected for the review. It was found that the contributions of IoT surpass the challenges of using IoT. Two significant contributions have been identified, which are facilitating communication and improving safety as well as improving quality of life. Meanwhile, the main challenges of IoT implementation are issues related to security and privacy. It was also found that there is a lack of information related to the ways to overcome the challenges, although the challenges were discussed in length. This review provides an overview of the adoption of IoT for Smart Living, focusing on its challenges and contribution.